Pengaruh Pembelajaran PAI Berbasis Moderasi Digital terhadap Sikap Kritis Narasi Keagamaan Ekstrem - Makmun, Agus; Cholid, Nur; Syaifudin, Muh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing exposure of students to extremist religious narratives through digital media poses serious challenges for Islamic Education (PAI). This study aims to examine the effect of digital moderation-based PAI learning on students’ critical attitudes toward extremist religious narratives. Employing a quasi-experimental design, the research involved two groups of senior secondary students: an experimental group receiving PAI instruction integrated with digital moderation principles and a control group experiencing conventional PAI learning. Data were collected using a validated critical attitude scale administered through pretest and posttest procedures. The collected data were analyzed using descriptive statistics, normality and homogeneity tests, independent samples t-tests, and normalized gain analysis. The results indicate a statistically significant difference between the experimental and control groups’ posttest scores (p < 0.05). Students who participated in digital moderation-based PAI learning demonstrated a higher level of critical attitudes, particularly in analyzing religious arguments, evaluating the credibility of digital sources, and rejecting absolutist and intolerant claims. Furthermore, the experimental group achieved a moderate to high improvement level, while the control group showed only low improvement. These findings suggest that integrating digital moderation into PAI learning effectively strengthens students’ critical attitudes toward extremist religious narratives. This study contributes to the development of Islamic education pedagogy by providing empirical evidence on the role of digital moderation in countering religious extremism within formal educational settings.